(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Acute respiratory diseases (ARDs) represent a significant global health burden, especially in vulnerable populations such as children, the elderly, and immunocompromised individuals. This article examines the nature of ARDs, their causative agents, clinical manifestations, and current approaches in diagnosis and treatment. Through a detailed review of scientific literature and empirical data, the study provides insight into effective public health strategies and clinical practices aimed at minimizing the impact of ARDs on communities.